Creating an anti-communist motion picture producers’ network in Asia : the Asia Foundation, Asia Pictures, and the Korean Motion Picture Cultural Association - Lee, Sangjoon (2020)
The Asia Foundation, a private non-profit organization, which was established in 1951, was actively involved in the motion picture industries in Asia since its first feature film project The People Win Through was produced and released in Burma in 1953. Roughly from 1953 to 1959, to win the battle for hearts and minds in Asia, The Asia Foundation had clandestinely supported anti-Communist motion picture industry personnel, ranging from producers, directors, and technicians to critics, writers, and general intellectuals in many parts of Asia. This article traces TAF’s motion picture project in Asia, focusing primarily on the early history of Asia Pictures in Hong Kong and Korea Motion Picture Cultural Association in post-Civil War Korea.